Vocational programs as transition to independent living for persons with mental retardation - Salvador, Kathleen Melissa Angeles (2005)
This study described the vocational programs that could lead to independent living in the absence of independent living programs in our country. Results of the study showed that school administrators have the knowledge and the experience in the implementation of vocational programs for PMR that could lead to independent living. However, teachers of the vocational programs need to gain more knowledge and experience in the implementation of the programs as their professional training was not in SPED. This was supported by findings that show that most practicing teachers today come from different fields or disciplines other than SPED. The responses of persons with MR showed that they strongly believed in the vocational programs being implemented in their schools.